Estimating the thermoneutral zone for broiler breeders using behavioral analysis - Pereira, Danilo Florentino [UNESP]; Naas, I. A. (Elsevier B.V., 2008)
Knowledge about bird's heat stress is extensively discussed in the literature. From behavior data collected during the summer of 2000/2001 in an open-sided reduced scale model of a poultry barn, this study estimated the thermoneutral zone for female broiler breeders. The birds were electronically identified and the frequency of use of passage, indicating movement, and drinker, indicating thirst, where the antennas were placed, was recorded. Environmental data such as dry and wet bulb temperature were collected in the geometric center of the model and continuously registered by a datalogger. From the statistical analysis, it was possible to predict a real-time-based zone where the birds showed coherent behavior towards the use of the drinker and movement in the passage. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: thermoneutral zone; bird's behavior; electronic identification